Composting domestic sewage using Trichoderma isolates were from agricultural soils - NGUYEN PHUONG THUY; NGUYEN NGOC TRAI (Society for Indonesian Biodiversity, 2025)
Abstract. Thuy NP, Trai NN. 2025. Composting domestic sewage using Trichoderma isolates were from agricultural soils. Biodiversitas 26: 1743-1753. This study aimed to evaluate the efficacy of Trichoderma spp. in enhancing the composting process of sewage sludge from domestic treatment plants. The research focused on improving organic matter decomposition and compost quality while addressing microbial safety. Thirteen Trichoderma isolates were screened from agricultural soils, with Trichoderma afroharzianum (isolate BCS3) identified as having the highest cellulase activity. Composting trials involved six treatments: one control, five sewage sludge combinations, and a T. afroharzianum BCS3 bioproduct. Parameters such as temperature, moisture content, pH, and the physicochemical and microbiological properties of the final compost were monitored throughout the 30-day process. All treatments completed the composting process with characteristic thermophilic phases. Treatment 3, featuring an optimal mix of sludge and T. afroharzianum BCS3 bioproduct, exhibited the most significant thermophilic activity, indicating enhanced microbial activity and rapid organic matter decomposition. Trichoderma-treated compost showed increased organic matter, improved nitrogen and phosphorus availability, and higher concentrations of humic substances. All composts met microbial safety standards, testing negative for E. coli and Salmonella. Trichoderma spp., particularly T. afroharzianum BCS3, significantly enhanced the composting of sewage sludge by accelerating organic matter breakdown and improving nutrient profiles. This sustainable approach offers an efficient solution for sludge management, producing high-quality organic fertilizer for agricultural use.